Military potential of biological toxins - Zhang, Xiujuan; Kuča, Kamil; Dohnal, Vlastimil; Dohnalová, Lucie; Wu, Qinghua; Wu, Chu (Journal of Applied Biomedicine, 2014)
Toxins are produced by bacteria, plants and animals for defense or for predation. Most of the toxins specifically affect the mammalian nervous system by interfering with the transmission of nerve impulses, and such toxins have the potential for misuse by the military or terrorist organizations. This review discusses the origin, structure, toxicity and symptoms, transmission, mechanism(s) of action, symptomatic treatment of the most important toxins and venoms derived from fungi, plants, marine animals, and microorganisms, along with their potential for use in bioweapons and/or biocrime. Fungal trichothecenes and aflatoxins are potent inhibitors of protein synthesis in most eukaryotes and have been used as biological warfare agents. Ricin and abrin are plant-derived toxins that prevent the elongation of polypeptide chains. Saxitoxin, anatoxin, and tetrodotoxin are marine-derived toxins that bind to sodium channels in nerve and muscle tissue and cause muscle paralysis. Most bacterial toxins, such as botulinum and Shiga affect either the nervous system (neurotoxins) or damage cell membranes. Batrachotoxins, which are secreted by poison-dart frogs are extremely potent cardiotoxic and neurotoxic steroidal alkaloids. The aim of this review is to provide basic information to enable further understanding of these toxins and their potential military uses.
Keywords: Toxins, Biological; Mycotoxins; Toxoids; Abrin; Saxitoxin; shiga toxiny; botulotoxiny; biologické bojové látky; ricin; mořské toxiny; Bacterial Toxins; T-2 Toxin; T-2 toxin; toxoidy; lidé; aflatoxiny; Venoms; Batrachotoxins; Shiga Toxins; abrin; saxitoxin; živočišné jedy; mykotoxiny; otrava; Poisoning; Biological Warfare Agents; Aflatoxins; Tetrodotoxin; Marine Toxins; Botulinum Toxins; tetrodotoxin; Ricin; bakteriální toxiny; biologické toxiny; batrachotoxiny; Humans